Reduced monocyte proportions and responsiveness in convalescent COVID-19 patients - Ravkov, Eugene V.; Williams, Elizabeth S. C. P.; Elgort, Marc; Barker, Adam P.; Planelles, Vicente; Spivak, Adam M.; Delgado, Julio C.; Lin, Leo; Hanley, Timothy M. (Frontiers in Immunology, 2024)
The clinical manifestations of acute severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection and COVID-19 suggest a dysregulation of the host immune response that leads to inflammation, thrombosis, and organ dysfunction. It is less clear whether these dysregulated processes persist during the convalescent phase of disease or during long COVID. We investigated the effects of SARS-CoV-2 infection on the proportions of classical, intermediate, and non-classical monocytes, their activation status, and their functional properties in convalescent COVID-19 patients and uninfected control subjects. We found that the percentage of total monocytes was decreased in convalescent COVID-19 patients compared to uninfected controls. This was due to decreased intermediate and non-classical monocytes. Classical monocytes from convalescent COVID-19 patients demonstrated a decrease in activation markers, such as CD56, in response to stimulation with bacterial lipopolysaccharide (LPS). In addition, classical monocytes from convalescent COVID-19 patients showed decreased expression of CD142 (tissue factor), which can initiate the extrinsic coagulation cascade, in response to LPS stimulation. Finally, we found that monocytes from convalescent COVID-19 patients produced less TNF-a and IL-6 in response to LPS stimulation, than those from uninfected controls. In conclusion, SARS-CoV-2 infection exhibits a clear effect on the relative proportions of monocyte subsets, the activation status of classical monocytes, and proinflammatory cytokine production that persists during the convalescent phase of disease.Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is the causative agent of coronavirus infectious disease 19 (COVID-19) As of August 2023, it has affected over 770 million people, resulting in nearly 7 million deaths worldwide (WHO Coronavirus (COVID) dashboard). The symptoms of the disease vary from mild to severe, depending on age, gender, physical health, and other host factors. Notably, a dysregulated host immune response is observed in COVID-19 patients, leading to complications like hyperinflammation, thrombosis,